The Distal and Proximal Role of Alcohol Use, Alcohol Expectancies, and Drinking Contexts in Sexual Assault Perpetration - (:unkn) unknown (My University, 2024)
Sexual assault is a major public health and criminal justice problem worldwide, in our society, and particularly among college students. The aim of the present study was to gain a deeper and more comprehensive understanding of the role of various alcohol-related factors in sexual assault perpetration, including problematic alcohol use, alcohol expectancies related to social facilitation and sexual enhancement, and drinking contexts, such as bars, clubs, parties, etc. Further, the present study assessed these factors in univariate and multivariate analyses and both distal and proximal to incidents of sexual assault. Participants were 275 college men who responded to a variety of questionnaires via a confidential online survey. Participants were categorized into one of three groups based on their level of endorsement of sexual assault perpetration behaviors during the past 12 months: non-perpetrators (n = 127), contact/coercion perpetrators (n = 104), and rape perpetrators (n = 44). Results indicated that frequent alcohol use, heavy episodic drinking, high endorsement of alcohol expectancies related to social facilitation and sexual enhancement, and frequent attendance of drinking contexts were all individually significantly predictive of sexual assault perpetration during the past 12 months, across both levels of sexual assault severity. However, multivariate analyses indicated that only three of these factors were uniquely predictive of sexual assault perpetration, namely, high endorsement of alcohol expectancies related to sexual enhancement, frequent attendance of drinking contexts, and frequent alcohol use. Additionally, results indicated that rape perpetrations, but not contact/coercion perpetrations, were significantly more likely than not to involve alcohol use at the time of the assault by both the perpetrator and the victim, and were significantly more likely to occur at, or immediately after leaving, a drinking context. The role of alcohol expectancies related to social facilitation and sexual enhancement proximal to sexual assault perpetration was inconclusive, due to the small sample size for those specific analyses. Implications for research on sexual assault generally, and particularly research investigating risk factors for sexual assault perpetration, as well as applications for intervention programs aimed at reducing sexual assault perpetration, are discussed.
Keywords: Alcohol expectancies; Alcohol use; Drinking contexts; Heavy episodic drinking; Sexual assault; Sexual assault perpetration